2022
DOI: 10.1093/pcp/pcac130
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinins Induce Prehaustoria Coordinately with Quinone Signals in the Parasitic Plant Striga hermonthica

Abstract: Orobanchaceae parasitic plants are major threats to global food security, causing severe agricultural damage worldwide. Parasitic plants derive water and nutrients from their host plants through multicellular organs called haustoria. The formation of a prehaustorium, a primitive haustorial structure, is provoked by host-derived haustorium-inducing factors (HIFs). Quinones, including 2,6-dimethoxy-p-benzoquinone (DMBQ) are of the most potent HIFs for various species in Orobanchaceae, but except non-photosynthet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 96 publications
2
24
0
Order By: Relevance
“…This was clearly supported by the inhibitory effect of ASBr and TFBQ on all of these HIFs (Figure 3) (Aoki et al, 2022). On the other hand, we found that LGR-991, a competitive inhibitor of CK that directly binds CK receptors, inhibited CKs, AS and SyA but not DMBQ (Figure 3) (Aoki et al, 2022). These results remarkably demonstrate the independence of quinone signaling transduction from CK perception and indicate that phenolic signaling is integrated into CK perception.…”
Section: Interaction Of Phenolic Signaling With Cytokinin Signalingsupporting
confidence: 64%
See 4 more Smart Citations
“…This was clearly supported by the inhibitory effect of ASBr and TFBQ on all of these HIFs (Figure 3) (Aoki et al, 2022). On the other hand, we found that LGR-991, a competitive inhibitor of CK that directly binds CK receptors, inhibited CKs, AS and SyA but not DMBQ (Figure 3) (Aoki et al, 2022). These results remarkably demonstrate the independence of quinone signaling transduction from CK perception and indicate that phenolic signaling is integrated into CK perception.…”
Section: Interaction Of Phenolic Signaling With Cytokinin Signalingsupporting
confidence: 64%
“…No detectable variation was found in the morphology of prehaustoria induced by phenolics, quinones or CKs, implying that their signaling must converge toward the same physiological output, at least in S. hermonthica. This was clearly supported by the inhibitory effect of ASBr and TFBQ on all of these HIFs (Figure 3) (Aoki et al, 2022). On the other hand, we found that LGR-991, a competitive inhibitor of CK that directly binds CK receptors, inhibited CKs, AS and SyA but not DMBQ (Figure 3) (Aoki et al, 2022).…”
Section: Interaction Of Phenolic Signaling With Cytokinin Signalingsupporting
confidence: 64%
See 3 more Smart Citations